Immune response of porcine alveolar macrophages to a concurrent infection with porcine reproductive and respiratory syndrome virus and Haemophilus parasuis in vitro - Kavanová, Lenka; Prodělalová, Jana; Nedbalcová, Kateřina; Matiašovic, Ján; Volf, Jiří; Faldyna, Martin; Salát, Jiří (Veterinary microbiology, 2015)
Porcine reproductive and respiratory syndrome virus (PRRSV) can predispose pigs to secondary respiratory infection with bacteria such as Haemophilus parasuis. Animals infected with both pathogens develop more severe clinical disease. The immune response of porcine alveolar macrophages (PAMs) to simultaneous infection with PRRSV and H. parasuis was analysed in vitro, describing cytokine production, expression of cell surface molecules, and production of reactive oxygen species (ROS). Concurrent infection with PRRSV and H. parasuis increased gene expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-8) in PAMs in comparison with PAMs infected with PRRSV or H. parasuis alone. An additive effect of dual infection on IL-1β production was confirmed at the protein level. PAMs infected with PRRSV showed increased production of ROS compared to controls. Conversely, simultaneous infection of PAMs with PRRSV and H. parasuis decreased production of ROS, indicating the presence of an H. parasuis defence mechanism against respiratory burst. Concurrent infection of PAMs with PRRSV and H. parasuis was shown to elicit a pro-inflammatory immune response represented by significant IL-1β production. Severe multifactorial respiratory disease in natural conditions caused by both pathogens could be the consequence of pro-inflammatory mediated immunopathology.
Keywords: kultivované buňky; messenger RNA; hemofilové infekce; Reactive oxygen species; alveolární makrofágy; cytokiny; Gene Expression Regulation, Bacterial; Gene Expression Regulation, Viral; Haemophilus Infections; Macrophages, Alveolar; Cytokines; Porcine respiratory and reproductive syndrome virus; Swine Diseases; nemoci prasat; regulace exprese virových genů; Cells, Cultured; reprodukční a respirační syndrom prasat; Swine; IL-1β; RNA, Messenger; zvířata; Haemophilus parasuis; PRRSV; biologické markery; koinfekce; regulace genové exprese u bakterií; Porcine alveolar macrophages; prasata; Porcine Reproductive and Respiratory Syndrome; Coinfection; Biomarkers; virus reprodukčního a respiračního syndromu prasat; Animals